Cardiovascular disease risk models and dementia or cognitive decline: a systematic review - Jia, Ruirui; Wang, Qing; Huang, Hengyi; Yang, Yanli; Chung, Yuet Foon; Liang, Tao (Frontiers in Aging Neuroscience, 2023)
Background: Health cognitive promotion and protection is a critical topic. With the world's aging population and rising life expectancy, many people will suffer from highly age-related dementia illnesses. Cardiovascular disease (CVD) and dementia share the same unhealthy lifestyles and metabolic factors; these recognized risks frequently co-occur. CVD risk models may have a close association with dementia and cognitive decline. So, this systematic review aimed to determine whether CVD risk models were connected with dementia or cognitive decline and compare various models' predictive ability.